Nature Relatedness as a Predictor of Psychological Well-Being: A Study of Indonesian Urban Society - Bartolomeus Yofana Adiwena; Ratna Djuwita (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
The complexity of urban life can have its own negative impact on the psychological well-being (PWB) of its society. It is thought that the natural environment can reduce that negative impact and have an important role in the health and well-being of urban society. Nature relatedness (NR) is a construct which illustrates an approach to, or a subjective individual relationship with, the natural environment. Previous research indicates that NR has a positive relationship with the PWB of a person; however such research used a sample of society in Western countries. Does a relationship between NR and PWB exist also in the context of urban Indonesian society? The principle aim of this research was to prove a relationship between NR and PWB, using a sample from urban Indonesian society. This research was of a non-experimental nature, with 178 respondents. Analysis using structural equation modeling (SEM) proved that the NR level of an individual is a positive predictor of the PWB they have. For this reason, the higher the level of NR an individual has, the higher also is the level of PWB they will have. The authors recommend that all people managing vested interests pay attention not only to situational factors, such as the existence of open green spaces and the cleanliness of the environment, but also pay attention to dispositional factors, such as NR, which is proven to have an important role for PWB.